If \(p,q,r\) are the roots of the equation

\[x^3-3px^2+3q^2x-r^3\]

Prove that \(p=q=r\).

Elementary proof:

By Vieta's Formula,

\(p+q+r=3p\)

\(pq+qr+rp=3q^2\)

\(pqr=r^3\)

From the third equation,

\(pq=r^2\)

Substitute to the second equation,

\(r^2+qr+rp=3q^2\)

\(r(p+q+r)=3q^2\)

\(3rp=3q^2\)

\(pr=q^2\)

Substitute \(pr=q^2\) into the third equation,

\(q^3=r^3\implies q=r\)

Again,

\(pq=r^2\)

\(pr=r^2\)

\(p=r \implies p=q=r\)

Can you find a better proof?

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestPut \(x=r\) in the equation. Since \(r\) is a root, we immediately get \(pr=q^2\) (assuming \(r\neq 0\)). Also \(pqr=r^3\). The rest follows from these two.

Log in to reply

Brilliant proof!!!

Log in to reply

Brilliant! @Abhishek Sinha

Log in to reply

we can assume that p=q . Which means that we are assuming p to be the repeated root of the given function . Differentiate the given cubic and let it be g(x). then substitute p in g(x) Since we have assumed p to be repeated root thus it will also be the root of g(x). on substituting p in the equation we will get p=q which concurs with our assumption.

Log in to reply

Indeed, I've found a much faster solution. Using the cubic formula, we get that

\[\begin{align*}x&=\sqrt[3]{\left(\frac{-(-3p)^3}{27(1)^3}+\frac{(-3p)(3q^2)}{6(1)^2}-\frac{(-r^3)}{2(1)}\right)+\sqrt{\left(\frac{-(-3p)^3}{27(1)^3}+\frac{(-3p)(3q^2)}{6(1)^2}-\frac{(-r^3)}{2(1)}\right)^2+\left(\frac{(3q^2)}{3(1)}-\frac{(-3p)^2}{9(1)^2}\right)^3}}\\&+\sqrt[3]{\left(\frac{-(-3p)^3}{27(1)^3}+\frac{(-3p)(3q^2)}{6(1)^2}-\frac{(-r^3)}{2(1)}\right)-\sqrt{\left(\frac{-(-3p)^3}{27(1)^3}+\frac{(-3p)(3q^2)}{6(1)^2}-\frac{(-r^3)}{2(1)}\right)^2+\left(\frac{(3q^2)}{3(1)}-\frac{(-3p)^2}{9(1)^2}\right)^3}}\\&-\frac{(-3p)}{3(1)}\\&=\sqrt[3]{p^3-\frac{3pq^2}2+\frac{r^3}2+\sqrt{\left(p^3-\frac{3pq^2}2+\frac{r^3}2\right)^2+\left(q^2-p^2\right)^3}}\\&+\sqrt[3]{p^3-\frac{3pq^2}2+\frac{r^3}2-\sqrt{\left(p^3-\frac{3pq^2}2+\frac{r^3}2\right)^2+\left(q^2-p^2\right)^3}}\\&+p\end{align*}\]

is one of \(p\), \(q\), and \(r\). We can find the other roots by dividing out, and the rest of the proof is omitted.

Log in to reply

Honestly, why do you love to bash out all the problems so much?

Log in to reply